PERBERDAYAAN KEPALA ADAT DALAM PENYELESAIAN SENGKETA TANAH KAMPUNG DOYO BARU DISTRIK WAIBU KABUPATEN JAYAPURA - Herniati , Herniati; Hartini , Sri Iin; Reliubun, Idris Firmansyah; Ingsaputro, Muhammad Hafiz (LPPM Uncen, 2023)
Legal counseling was carried out by the Extension Team from Doctor Husni Ingratubun University, with the title